Financial behavior and problems among academy of contemporary Islamic studies (ACIS) students in UiTM Puncak Alam / Amira Nursyafika Azman - Azman, Amira Nursyafika (2019)
This study is about the financial behavior and problems among Academy of Contemporary Islamic Studies (ACIS) students in University of Teknologi Mara Puncak Alam. This study is given priority to ACIS students who have only two courses namely Diploma in Muamalat and Diploma in Halal Management. It is focused only for the semester 3, 4 and 5. This is because semester 1 and 2 are not available at UiTM Puncak Alam but they have been transferred to other universities that receive courses for this ACIS. The total number of students involved is more than 300 (population) but however this study takes only 50 (samples) over 300. This is due to short time and difficult to make a comparison on it. This study used both methods to get the results which are qualitative and quantitative. Qualitative is referred to articles from previous researchers, newspaper and some books. Whilst, quantitative is the questionnaire that distributed to the students through online (WhatsApp group). The results showed that mostly financial problems was influenced by group of family, friends and personal’s attitude that like to spend. Hence, there is still a lot of effort required in order to reduce all of these problems that affecting someone’s finance.